Influence of land access on climate-smart agriculture for low-emission food systems: A sustainable livelihood perspective - Ngaiwi, Mary (2024)
Climate change poses significant risks, manifesting in extreme weather events, armed conflicts, and economic instability, hindering sustainable livelihoods. Land tenure challenges impede the adoption of climate-smart agriculture in rural areas. This research explores the impact of land tenure systems and institutional factors on low-emission food systems (LEFS) adoption. Investigating secure land tenure, optimal land size, resource access equity, collaborative land governance, and climate-conscious land use planning, the study identifies mechanisms contributing to LEFS implementation. The findings offer valuable insights into land tenure's role in promoting sustainable livelihoods and resilient agriculture amid climate change challenges.